Criminal liability of legal persons in light of the subsidiarity of criminal repression - Pavel Kotlán (DANUBE: Law, Economics and Social Issues Review, 2016)
This paper deals with the definition of (substantive) subsidiarity of criminal repression and the possibility of its application to the criminal liability of legal persons. After defining the liability of legal persons in the relevant legal regulations, the paper presents an interpretation of subsidiarity in Section 12(2) of the Criminal Code that is significantly different from the "official" opinion. Subsequently, the paper discusses certain criminal law situations in which the application of subsidiarity would lead to the conclusion that the legal person is not punishable ("non-criminality"). The first aim was thus to present the theoretical concept of subsidiarity of criminal repression, which would be methodologically correct, and therefore generally applicable. The second objective was directed at demonstrating that this construct can be applied to specific examples of the liability of legal persons, that is, that it can be applied to the activities of the bodies in charge of criminal proceedings.
Keywords: 330; Subsidiarity; Criminality; Legal Person